2017
DOI: 10.1177/0165025417690264
|View full text |Cite
|
Sign up to set email alerts
|

Immigrant status, gender, and school burnout in Finnish lower secondary school students

Abstract: The aim of this longitudinal study among 9,223 students from 7 th to 9 th grade (age 13-16) was to assess whether immigration status and gender are associated with the level and change (slope) in school burnout among lower secondary school students in the Helsinki metropolitan area. 97% of the variation in school burnout was attributable to individual factors. Both the intercept (2.3, p < 0.001) and slope (0.5, p < 0.001) of school burnout were statistically significant. The slope showed increasing school burn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 31 publications
4
32
0
8
Order By: Relevance
“…From this viewpoint, academic buoyancy and adaptive emotion regulation strategies have an analogous interaction effect on students with higher general cognitive ability. Previous studies have also reported that successful students can be more prone to academic burnout while reporting more depressive symptoms and higher level of stress, and/or higher performance orientation (Salmela-Aro et al, 2018;Tuominen-Soini & Salmela-Aro, 2014;Tuominen-Soini, Salmela-Aro, & Niemivirta, 2008) or lower academic buoyancy (Vinter et al, 2019). This pattern refers to the possible problem quite many Estonian middle school students may have: although they have shown excellent results in PISA studies (OECD, 2016), they may be more prone to academic burnout under pressure to achieve academically, especially when they have low social-emotional skills.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…From this viewpoint, academic buoyancy and adaptive emotion regulation strategies have an analogous interaction effect on students with higher general cognitive ability. Previous studies have also reported that successful students can be more prone to academic burnout while reporting more depressive symptoms and higher level of stress, and/or higher performance orientation (Salmela-Aro et al, 2018;Tuominen-Soini & Salmela-Aro, 2014;Tuominen-Soini, Salmela-Aro, & Niemivirta, 2008) or lower academic buoyancy (Vinter et al, 2019). This pattern refers to the possible problem quite many Estonian middle school students may have: although they have shown excellent results in PISA studies (OECD, 2016), they may be more prone to academic burnout under pressure to achieve academically, especially when they have low social-emotional skills.…”
Section: Resultsmentioning
confidence: 98%
“…Associations between academic burnout and general cognitive ability have not been researched a lot but it has been shown that academic burnout is related to lower level of academic achievement (May, Bauer, & Fincham, 2015;Salmela-Aro et al, 2008;Salmela-Aro, Read, Minkkinen, Kinnunen, & Rimpela, 2018;Tuominen-Soini & Salmela-Aro, 2014) and diminished attention and problem solving skills (May et al, 2015). However, the associations between academic burnout and academic achievement (as well as general cognitive ability) are not consistent in every study.…”
Section: Associations Between Academic Burnout and General Cognitive mentioning
confidence: 99%
See 1 more Smart Citation
“…It can be claimed that the burnout of students may have some negative consequences such as getting tired of school activities quickly, developing negative attitudes towards school and school activities, emergence of a feeling of insufficiency, cynicism, low motivation, decrease in self-control, depression, low participation and success (Aypay, 2018b;Cooper, Seibert, May, Fitzgerald & Fincham, 2017;Fiorilli, De Stasio, Di Chiacchio, Pepe & Salmela-Aro,2017;Lee, Puig, Kim, Shin, Lee and Lee, 2010;Salmela-Aro, Read, Minkkinen, Kinnunen & Rimpelä, 2018).…”
Section: Discussion and Conclusion On The First Hypothesismentioning
confidence: 99%
“…Students' academic achievement is influenced by many variables. Students' school burnout (Atik, 2016;Demir and Gencdogan, 2017;Galbraith and Merrill, 2014;Kutsal and Bilge, 2012;Lin and Huang, 2013;Salmela-Aro, Kiuru, Pietikäinen and Jokela, 2008;Salmela-Aro, Read, Minkkinen, Kinnunen and Rimpelä, 2018) and their trust in their teachers (Adams, 2013;Bryk and Schneider, 2002;Dewulf, van Braak and Van Houtte, 2017;Goddard, Salloum andBerebitsky, 2009 Hoy andTschannen-Moran, 2007;McKinney and Berube, 2018) have been identified as important factors in their success.…”
Section: Introductionmentioning
confidence: 99%